HEREDITARY NON-POLYPOSIS COLORECTAL CANCER (LYNCH SYNDROME) PADA WANITA UMUR 16 TAHUN - Asril Zahari; Sudiyatmo Sudiyatmo (Faculty of Medicine, Universitas Andalas, 2011)
AbstrakKanker kolorektal menduduki peringkat ketiga jenis kanker yang paling sering terjadi di dunia. Sekitar 3% kasus kanker kolorektal merupakan jenis hereditary non polyposis colorectal cancer (HNPCC)/Lynch syndrome, yang sering muncul pada usia muda. Dilaporkan satu kasus di rumah sakit Dr. M. Djamil Padang, wanita berumur 16 tahun dengan keluhan nyeri perut kanan bawah. Didapatkan riwayat penyakit serupa pada kakek, bibi pasien dan enam anggota keluarga yang lain. Pada pemeriksaan fisik abdomen teraba massa dengan konsistensi keras dan terfiksir. Pada kolonoskopi dan biopsi ditemukan tumor jenis adenocarcinoma colon moderatly differentiated di fleksura hepatika dan polip di kolon sigmoid. Berdasarkan kriteria Amsterdam pasien didiagnosa Lynch syndrome. Pada Pasien dilakukan subtotal kolektomi, anastomose ileorectal dan kemoterapi ajuvan. Identifikasi genetik sedang dikerjakan untuk melihat adanya kelainan genetik pada pasien. Pasien melakukan skrining berkala untuk mencegah kanker HNPCC jenis yang lain.Kata kunci : Hereditary non polyposis colorectal cancer, Lynch syndrome, Microsatellite instability, skrining.AbstractCarcinoma colorectal is the third most common type of cancer that occurs in the world. About 2% -3% of cases of colorectal cancer is hereditary non-polyposis colorectal cancer (HNPCC)/Lynch syndrome, which often appear at a young age. Amsterdam and Bethesda criteria have been used to identify patients with Lynch syndrome.one case was reported at the Dr. M. Djamil Padang hospital, a 16-year-old girl with right lower abdominal pain. Obtained a history of similar disease in grandparents, aunts and six other family members. On physical examination found palpable fixed abdominal mass with hard consistency in the lower right abdomen. At colonoscopy and biopsy found a moderatly differentiated adenocarcinoma colon type at the hepatic flexure and the sigmoid colon polyp. Based on the Amsterdam criteria, patients diagnosed with HNPCC/Lynch syndrome. Patients treated with subtotal colectomy, ileorectal anastomose and adjuvant chemotherapy.LAPORAN KASUS173Genetic identification is underway to see any genetic abnormalities. Patients be screened regularly to prevent other types of cancer HNPCC.Key word : Hereditary non-polyposis colorectal cancer, Lynch syndrome, Microsatellite instability, screening.